La relazione percettiva nella fenomenologia sperimentale - Ferro, Floriana (Aesthetica Preprint, 2021)
The paper is focused on the concept of perceptual relation according to experimental phenomenology, belonging to Gestaltist and ecological traditions. First of all, it will be shown the meaning of “relation” in the perceptual domain, including a specific definition of object and subject. For this purpose, the paper will present the difference with the representationalist perspective, which challenges immediate experience and the perception of unified objects. Secondly, the concept of “perceptual relation” will be compared to the idea of Gestalttheorie’s “intrinsic relation”. It will be sustained that perceptual relations do not concern only connections between the parts and the whole of a configuration, but they extend to otherness, namely perceptual object, other subjects, and the Umwelt. For this purpose, the paper will provide some examples of ambiguity of the relation ground-figure, especially reversible and bistable figures.